Increased hospital documentation requirements may not increase breastfeeding among first‐time mothers. Issue 2 (16th October 2015) - Strauch, Jessica; Rohrer, James E.; Refaat, Amany
Abstract: Rationale, aims and objectives: To examine if initiation of breastfeeding and exclusive breastfeeding on discharge in first‐time mothers increased after a change in hospital policy increased reporting requirements about breastfeeding by new mothers. Methods: Five hundred women that gave birth to their first child were studied, with half giving birth prior to reporting requirements and half giving birth after the reporting began. After implementing mandatory reporting requirements through an accrediting body, an increase in maternity care practices designed to promote breastfeeding was expected. Medical records of those women were reviewed to identify key variables, including age, race/ethnicity, marital status, education level, health insurance, type of delivery, gestational age, initiation of breastfeeding and exclusive breastfeeding throughout the hospital stay. Results: There was an 18.7% increase in initiation of breastfeeding the year the mandatory reporting began. However, there was a 5.9% decrease in exclusive breastfeeding that year. The odds of initiating breastfeeding were greater after implementation of mandatory reporting measures (OR = 2.07; P  = 0.0007), yet the odds for exclusive breastfeeding on discharge did not show a statistically significant change (OR = 0.94; P  = 0.7507). Other variables that had a significant effect on both initiation and exclusive breastfeeding included being non‐Hispanic white, other race/ethnicity category, marital status and type of insurance (exclusive breastfeeding only). Conclusion: Professional support that can be offered to new mothers may have a positive effect on their decision to breastfeed. However, a hospital policy change that increases reporting requirements may not have long‐term impact on breastfeeding. Longer term studies and multisite studies are needed.